COMPARISON OF THE FACTORS OF DEBRIS FLOWS FORMATION IN TYSA RIVER BASIN (ZAKARPATSKA AREA) - Guda, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Main factors of debris flow formation of Tysa river basin in Tyachuvskyu and Volovetskyu regions of Zakarpatska area have been determined and analyzed. The dangerous geological processes that have been formed in 1998–1999, 2006 and are formed today were considered. The detailed characteristics of geological and geomorphologic structure of the studied area are given. The necessity of classification of debris flows in the Carpathian region including hydrological features of debris flows' basins is confirmed. It was emphasized that the methods of debris flow prediction and influence must be divised taking into consideration particularities of classifications.